"Rock temple on Elephant Island". : Felsentempel auf Elephanta. - Unknown Studio (University of Southern California Digital Library (USC.DL), 2012)
Note: In oberer linker Ecke ist fehlender Teil der Negativglasplatte erkennbar. (BFN 10.1998).; Note translation: You can see that the negative plate has been damaged on the top left-hand corner. (BFN 10.1998).